Religio-spirituality and the coming-out process - Jones, Camilla H. (Kansas State University, 2008)
The purpose of this phenomenological research study was to describe and to understand religio-spirituality in the coming-out process for homosexual, bisexual, and transgender college students. The three research questions were as follows: (1) What have religious affiliations taught traditional college-aged lesbian, gay, bisexual, and transgender (LGBT) students about homosexuality?; (2) In what ways does a person's religio-spiritual life hinder/enhance the sexual identity development process and the coming-out process for a traditional college-aged student?; and (3) In what ways does the traditional college-aged LGBT student's religio-spirituality change through the process? Following completion of semi-structured interviews of 15 participants, the researcher acknowledged the emergence of nine categories that explain the essence of the coming-out process and its connection with religio-spirituality: (1) a noticeable societal influence on lesbian, gay, bisexual, or transgender (LGBT) beliefs, (2) an evident family influence on LGBT beliefs, (3) a direct church influence on LGBT beliefs, (4) a difficulty in merging sexuality and religio-spirituality, (5) a feeling of guilt for being an LGBT individual, (6) religio-spirituality affects when and to whom to come-out, (7) many leave the church after coming-out, (8) a feeling of need to protect family still in church after coming-out, and (9) an attempt to maintain a relationship with God or higher being without a relationship in a church or religious institution. These nine conclusions develop the essence of the coming-out process and religio-spirituality. Individuals in the coming-out process find themselves at a divide in their lives and they must decide which path to follow or attempt to make the paths intersect. The coming-out process is often an internal debate of whether they are LGBT, whether to come-out, and whether they should leave a church or change religio-spirituality. In student affairs, administers, counselors, and campus ministers can use data and conclusions from this research to understand the coming-out process and the overlapping nature of religio-spiritual identity and sexual identity. The researcher concludes that these professionals must have an understanding of the stages of growth for LGBT students as they attempt to come-out to friends and family as well as possibly maintain a religio-spiritual identity.
Keywords: Coming out; Religion; Spirituality; Sexuality; Education, Higher (0745)